RhIII‐Catalyzed Decarboxylative o‐Acylation of Arenes Bearing an Oxidizing Directing Group. Issue 24 (19th June 2019) - Bera, Suvankar; Chandrasekhar, K.; Chatterjee, Satadru; Killi, Sunil Kumar; Sarkar, Debabrata; Banerji, Biswadip
Abstract : Here in we report, rhodium(III)‐catalyzed decarboxylative acylation of arenes using α‐oxocarboxylic acids as acyl surrogate. In this strategy, O–NHAc group act as an autocleavable oxidizing directing group (ODG auto ), thus giving rise to ortho ‐acylated phenols in moderate to good yields. Mechanistic studies provided strong support for a kinetically relevant C–H bond activation. According to the best of our knowledge, this is the first report of Rhodium catalyzed decarboxylative acylation. Abstract : We present the first report of Rh III ‐Catalyzed Decarboxylative Acylation of arenes. This method provides an efficient access to both of mono/bis‐ ortho acylated phenols selectively. In general, for para ‐substituted N ‐aryloxyacetamides, the product selectivity towards mono and bis‐acylated phenols can be controlled by varying the amount of oxidant. But ortho ‐ and meta ‐substituted N ‐aryloxyacetamides give exclusive mono‐acylated product at any condition.